Postnatal Growth of Moroccan Preterm Infants: Determinants of Incomplete Catch-up Growth and Z-Score Trajectories in a Middle-Income Country. - Mochhoury, Latifa; Elgoundali, Khaddouj; Chebabe, Milouda; Chafik, Kawtar; Chahboune, Mohamed; Barkat, Amina (Journal of Research in Health Sciences)
Background: Prematurity and neonatal hypotrophy (defined as a Z-score below -2 for weight, length, or head circumference) increase the risk of perinatal morbidity, mortality, and long-term developmental disorders. This study examines the growth trajectories of Moroccan preterm infants and investigates the factors influencing their overall growth outcomes at six months, including weight, length, and head circumference. Study Design: A retrospective longitudinal cohort study Methods: This study was conducted at the National Reference Center for Neonatology and Nutrition in Rabat from April to October 2023. It included 686 premature newborns (24-36 weeks) hospitalized for ≥ 48 hours, with complete anthropometric data and follow-up of six months. Exclusion criteria were major malformations, chromosomal abnormalities, metabolic disorders, and incomplete data. ANOVA and multivariate logistic regression identified independent predictors of weight growth outcomes at six months (WAZ ≥ -2), adjusting for confounders (gestational age, gender, hospitalization, multiparity, phototherapy, antibiotics, and early food diversification). Results are reported as odds ratios (ORs) with 95% confidence intervals (CI). Growth curves were generated with Python. Significance was set at P < 0.05. Results: Gestational age of ≥ 32 weeks (OR = 6.66, 95% CI: 1.21, 36.72; P = 0.029) and multiparity (OR = 12.09, 95% CI: 2.12, 68.93; P = 0.005) predicted growth outcomes, while a hospital stay of ≥ 10 days reduced the likelihood (OR = 0.05, 95% CI: 0.01, 0.27; P = 0.001). Male gender and antibiotic use showed non-significant trends (P = 0.053). Conclusion: Close monitoring and targeted nutritional strategies are essential to improve postnatal growth in preterm infants.